SINDROME DE MAY-THURNER ASSOCIADO A UM SINDROME DE NUTCRACKER: CASO CLINICO E REVISÃO DA LITERATURA - Machado, Miguel (2017)
Introduction: The May Thurner syndrome (MTS), results from compression of left common iliac vein (LCIV) between the fifth lumbar vertebra, posteriorly, and the right common iliac artery (RCIA), anteriorly. This phenomenon can cause venous stasis in the pelvis and in the left lower limb. The Nutcracker syndrome (NCS) result from compression of the left renal vein (LRV) between the superior mesenteric artery and the aorta, called Anterior NCS, or more rarely by compression of the LRV between the aorta and the lumbar vertebra, when the vein passes behind the aorta, called posterior NCS. The association of the two anomalies can occur when a circunaortic renal vein exists. This phenomenon can cause stasis in the kidney and in the pelvis. The MTS and NCS are rare clinical entities and the association of the two pathologies is extremely rare. Clinical Case: A 29-year-old female, complaints of bilateral leg pain, predominantly on the left side, left malleolar edema which increases in the end of the day, and dyspaneuria. These complaints interfere severely with the quality of life of the patient. The physical examination reveals collateral varices in the posterior aspect of the left tight, a right side vulvar varicose vein and mild left malleolar edema.  A phlebography of the ilio-cava system and the ovarian vein reveal a compression of LCIV by the RCIA with an extensive collateral pathway communicating the left and the right vein iliac system, the origin of a right side vulvar varicose vein in the right internal iliac vein and the compression of a posterior LRV by the aorta. A transluminal angioplasty with sequential dilatation with a 12, 14 and 16 mm balloon was done and an Optimed stent 16/100 mm was implanted in the LCIV.At 3 months of follow up, the patient called and informed that she was pregnant, so she stopped the rivaroxabane and maintained the elastics stockings. The pregnancy and the child birth had no intercurrences. An abdomino-pelvic control CT at 12 months follow-up was done, showing the stent in a good position and patent, and posteriorly she was submitted to stab avulsion of varicose veins in the left thigh. At 18 months follow-up, the patient was clinically asymptomatic. Discussion/Conclusion: Insufficient knowledge about the natural history of NCS and MTS results from the   uncertainty in the diagnostic criteria and treatment selection, particularly in the rare association of both. This association can be responsible for the amplification of the symptomatology of the venous obstruction.  In our case, we have seen the resolution of the complaints by treating only one of the obstructive lesion (MTS) and we haven’t seen any effect of the pregnancy in the structure and patency of the ilio-caval stent.